ANALISIS PENGGUNAAN SHOPEE PAYLATER DI KALANGAN MAHASISWA DALAM PERSPEKTIF RIBA - Alief Pratama, Rexy; Anna Marisa Eriyani Iskandar, Putri; Nurhidayah Somantri, Annisa; Marlina, Lina (At-Tawazun, Jurnal Ekonomi Syariah, 2025)
Islam prohibits usury because it is considered a practice that disrupts economic fairness. Within the digital economy ecosystem, the Shopee PayLater feature has sparked sharia-related concerns due to the application of interest charges and late payment penalties. This study employs a descriptive-analytical literature review to examine the Shopee PayLater system from the perspective of riba. The findings reveal that its installment mechanism indicates the presence of riba and potential elements of gharar, making it inconsistent with Islamic muamalah principles. Among university students, the service also stimulates consumptive tendencies and financial vulnerabilities—such as impulsive spending, growing debt burdens, financial stress, social tension, and risks related to personal data security. The interest-based installments, penalty fees, and insufficiently transparent terms suggest the presence of riba and gharar, which contravene key muamalah values such as justice, clarity, and mutual consent. Although Shopee PayLater offers convenient access to goods without upfront payment, it poses risks for users from both sharia and digital economic perspectives.